Measurements of the suppression and correlations of dijets in Xe+Xe collisions at √sNN=5.44 TeV - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Castillo, Florencia Luciana; Czurylo, Marta; Rio, Fernando del; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Klassen, Martin; Mkrtchyan, Tigran; Ott, Philipp; et al. (Physical review, 2023)
Measurements of the suppression and correlations of dijets is performed using 3µ⁢b−1 of Xe+Xe data at √𝑠𝑁⁢𝑁=5.44 TeV collected with the ATLAS detector at the CERN Large Hadron Collider. Dijets with jets reconstructed using the 𝑅=0.4 anti-𝑘𝑡 algorithm are measured differentially in jet 𝑝T over the range of 32 to 398 GeV and the centrality of the collisions. Significant dijet momentum imbalance is found in the most central Xe+Xe collisions, which decreases in more peripheral collisions. Results from the measurement of per-pair normalized and absolutely normalized dijet 𝑝T balance are compared with previous Pb +Pb measurements at √𝑠𝑁⁢𝑁=5.02 TeV. The differences between the dijet suppression in Xe+Xe and Pb +Pb are further quantified by the ratio of pair nuclear-modification factors. The results are found to be consistent with those measured in Pb +Pb data when compared in classes of the same event activity and when taking into account the difference between the center-of-mass energies of the initial parton scattering process in Xe+Xe and Pb +Pb collisions. These results should provide input for a better understanding of the role of energy density, system size, path length, and fluctuations in the parton energy loss.
The ATLAS collaboration: G. Aad, L.M. Baltes, F. Bartels, F.L. Castillo, M.M. Czurylo, F. Del Rio, S. Dittmeier, M. Dunford, S. Franchino, M. Klassen, T. Mkrtchyan, P. Ott, D.F. Rassloff, S. Rodriguez Bosca, C. Sauer, A. Schoening, H.C. Schultz-Coulon, V. Sothilingam, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, J. Zinsser [und 2877weitere]
Gesehen am 30.06.2025
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol